Mengenal Potensi Ulat Maggot BSF di Kabupaten Labuhan Batu - Rehulina Sitepu (SUAN PUBLISHER, 2024)
This study aims to identify and analyze the potential for developing Black Soldier Fly (BSF) maggots (Hermetia illucens) as a solution for managing organic waste and an alternative source of protein in Binjai City. Cities in Indonesia face serious problems related to the accumulation of organic waste, while on the other hand, the need for quality animal and fish feed continues to increase. BSF maggots offer an innovative solution to both problems through their ability to degrade organic waste and their high nutritional value. This study will use qualitative and quantitative methods (mixed methods) with data collection techniques in the form of surveys, in-depth interviews, and observations. Data will be analyzed descriptively and SWOT to identify strengths, weaknesses, opportunities, and threats in the development of BSF maggots in Binjai City. Predictive results show that the potential for BSF maggots in Binjai City is very large, especially supported by the availability of organic waste, but faces challenges in terms of production scale and market acceptance. This study is expected to provide strategic recommendations for the city government and the community to optimize the potential of BSF maggots for sustainable development.